Borsvoeding - S. Delport (AOSIS, 1979)
Breast-feeding is an integral part of our mammalian heritage and consequently probably essential for the welfare of the newborn baby. Most of us are aware of the unbelievable advantages of breast-feeding but yet very few of us care to promote it consciously and actively. 1979 being Health Year as well as the International Year of the child offers the ideal opportunity to encourage this most rewarding experience of motherhood.